2020
DOI: 10.1002/jqs.3192
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between marine productivity and terrestrial input records in the Gulf of California over the last 28 ka

Abstract: We study the marine and terrestrial contributions in the Gulf of California (GC) to understand the relationship between continental climate and oceanographic variability over the last 28 ka. In Core AII125‐8‐JPC‐20, we examine aeolian and riverine inputs as nutrients for biological productivity. We use biogenic silica (%opal), total organic carbon (%TOC) and calcium carbonate (%CaCO3) as proxies for primary productivity, and lithic fraction distributions as proxies for terrigenous transport. At the core site, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(179 reference statements)
0
2
0
Order By: Relevance
“…In a regional context, during this period oceanographic conditions for the Gulf of California presented great variability within the water column, inferred from the association of diatoms, silicoflagellates and coccolithophores, as well as geochemical variables that is, organic carbon and biogenic opal versus calcium carbonate. Specifically, biogenic opal content exhibited an increase from 22% to 27% in the period between 7857 BP (30.1°C; −2.2 ± 0.4‰) and 6945 BP (28.2°C; −1.7 ± 0.1‰)(Álvarez et al, 2012; Arellano-Torres et al, 2020; Barron et al, 2005; Pérez-Cruz and Urrutia-Fucugauchi, 2009), suggesting a shallowing thermocline, coinciding with an increased presence of the diatom R. tesselata and the silicoflagellate D. stapedii , both indicators of a colder and slightly more saline water column (Barron et al, 2005; Schrader et al, 1986). Additionally, La Niña-like oceanographic conditions and decreased SSTs were recorded for the Gulf of California (Barron et al, 2005), the eastern margin of the Baja California peninsula (Arellano-Torres et al, 2020; Marchitto et al, 2010), and the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In a regional context, during this period oceanographic conditions for the Gulf of California presented great variability within the water column, inferred from the association of diatoms, silicoflagellates and coccolithophores, as well as geochemical variables that is, organic carbon and biogenic opal versus calcium carbonate. Specifically, biogenic opal content exhibited an increase from 22% to 27% in the period between 7857 BP (30.1°C; −2.2 ± 0.4‰) and 6945 BP (28.2°C; −1.7 ± 0.1‰)(Álvarez et al, 2012; Arellano-Torres et al, 2020; Barron et al, 2005; Pérez-Cruz and Urrutia-Fucugauchi, 2009), suggesting a shallowing thermocline, coinciding with an increased presence of the diatom R. tesselata and the silicoflagellate D. stapedii , both indicators of a colder and slightly more saline water column (Barron et al, 2005; Schrader et al, 1986). Additionally, La Niña-like oceanographic conditions and decreased SSTs were recorded for the Gulf of California (Barron et al, 2005), the eastern margin of the Baja California peninsula (Arellano-Torres et al, 2020; Marchitto et al, 2010), and the present study.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) found that atmospheric loading of dissolved inorganic nitrogen and total phosphorus, mostly derived from local sources, may support algal blooms in Utah Lake and become a major contributor to lake eutrophication—a condition that may advance cyanobacteria prevalence (Ren et al., 2020). Impact of dust inputs on marine phytoplankton productivity and biological C‐pump is evident from a sedimentological study in the Gulf of California (Arellano‐Torres et al., 2020). Also, organic nitrogen makes up a large portion of total N in wet and dry deposition (Matsumoto et al., 2019).…”
Section: Effects On Environmental Healthmentioning
confidence: 99%